2009
DOI: 10.2337/dc09-0627
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Reduce the Number of Cases of Missed Postpartum Diabetes in Women With Recent Gestational Diabetes Mellitus?

Abstract: OBJECTIVEUp to 30% of women with recent gestational diabetes mellitus (GDM) remain glucose intolerant after delivery. However, the rate of postpartum oral glucose tolerance tests (ppOGTTs) is low. Our aim in this study was to develop a model for risk assessment to target women with high risk for postpartum diabetes.RESEARCH DESIGN AND METHODSIn 605 Caucasian women with GDM, antenatal obstetrical and glucose data and the glucose data of the ppOGTTs performed 13 weeks (median) after delivery were prospectively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 23 publications
4
38
1
4
Order By: Relevance
“…The rate of lactation is low in European women, and this needs to be addressed. Similarly, uptake rates of post partum OGTT after GDM remain low internationally (5,34). Electronic alerts via text message or email, automated letters, and nurse phone contact may increase uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of lactation is low in European women, and this needs to be addressed. Similarly, uptake rates of post partum OGTT after GDM remain low internationally (5,34). Electronic alerts via text message or email, automated letters, and nurse phone contact may increase uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This is also expressed in our study. The study has also shown that high levels of blood sugar in pregnant women can risk developing diabetes or impaired glucose tolerance after pregnancy because, in women who have experienced a higher level of FBS during pregnancy, there has been impaired fasting glucose after pregnancy or diabetes; thus, this relationship proved significant (21).…”
Section: Discussionmentioning
confidence: 96%
“…The reasons for this difference can be due to the smaller sample size of our study compared with this study and having a control group in this study (20). Schaefer-Graf et al conducted another study that examines the factors involved in postpartum diabetes and how to reduce its patients (21). This study has shown that BMI is closely associated with the incidence of postpartum diabetes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, the rate of incidence of postpartum DM development in the first year among patients treated with insulin for GDM was found to be higher than that of other patients (p<0.05 OR=7.27). The necessity of insulin use during pregnancy was also defined as a factor with high predictive value for the development of DM in the future in the literature (9,21,(28)(29)(30). The total number of hospitalisation days and polyclinic control were evaluated since they consequently show poor glycemic control and the necessity of more common assessment, but there was no significant difference between patients diagnosed with DM and those not diagnosed with DM.…”
Section: Discussionmentioning
confidence: 99%